A template for constructing Bayesian networks in forensic biology cases when considering activity level propositions. (March 2018) - Taylor, Duncan; Biedermann, Alex; Hicks, Tacha; Champod, Christophe
Highlights: We provide a Bayesian network construction methodology for forensic DNA results. The methodology features evaluation given competing activity propositions. Our modelling approach leads to network architectures containing standard elements. We demonstrate the process on a mock case scenario. Abstract: The hierarchy of propositions has been accepted amongst the forensic science community for some time. It is also accepted that the higher up the hierarchy the propositions are, against which the scientist are competent to evaluate their results, the more directly useful the testimony will be to the court. Because each case represents a unique set of circumstances and findings, it is difficult to come up with a standard structure for evaluation. One common tool that assists in this task is Bayesian networks (BNs). There is much diversity in the way that BN can be constructed. In this work, we develop a template for BN construction that allows sufficient flexibility to address most cases, but enough commonality and structure that the flow of information in the BN is readily recognised at a glance. We provide seven steps that can be used to construct BNs within this structure and demonstrate how they can be applied, using a case example.